First time identification of Pandoraea sputorum from a patient with cystic fibrosis in Argentina: A case report - Martina, Pablo Francisco (2017)
Background: Pandoraea species are considered emerging pathogens in the context of cystic fibrosis (CF) and are difficult to identify by conventional biochemical methods. These multidrug resistant bacteria remain poorly understood particularly in terms of natural resistance, mechanisms of acquired resistance and impact on the prognosis of the disease and the lung function. Among them, Pandoraea sputorum has been previously described in few cases of CF patients from Spain, Australia, France and United States, underlining the need of more clinical data for a better knowledge of its pathogenicity. This is the first report relating to P. sputorum in a CF patient in Argentina. Case presentation: Pandoraea sputorum was identified in a nine-year-old cystic fibrosis patient from Argentina, after treatment failure during an exacerbation. The isolates were successfully identified by combining molecular techniques based on 16S rRNA sequencing and mass spectrometry (MS) methods, after reassessing previous misidentified isolates by conventional methods. After first isolation of P. sputorum, patient's clinical condition worsened but later improved after a change in the treatment. Although isolates showed susceptibility to trimethoprim-sulfamethoxazole and imipenem, in our case, the antibiotic treatment failed in the eradication of P. sputorum. Conclusions: All combined data showed a chronic colonization with P. sputorum associated to a deterioration of lung function. We noted that the presence of P. sputorum can be underestimated in CF patients and MALDI-TOF MS appears to be a promising means of accurate identification of Pandoraea species.